The Relationship Between Profitability Ratios and Dividend Policy in Consumption Sector Enterprises - Siti Aisyah (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the relationship between profitability ratios and dividend policy in companies operating in the consumption sector. The main focus of this research is to examine whether high profitability significantly influences the dividend policy implemented by companies. The profitability ratios used in this study include Return on Assets (ROA) and Return on Equity (ROE), while dividend policy is measured through Dividend Payout and Dividend Yield. Using multiple linear regression analysis, this study found that all the variables tested have a significant impact on the company's dividend policy. The analysis results show that companies with higher profitability tend to pay higher dividends, reflecting strong financial stability. This study also examines other aspects such as financial stability, which plays an important role in the company's ability to consistently pay dividends. The findings provide valuable insights for company managers in formulating an optimal dividend policy that can enhance shareholder value.